Enterprise Activity Modeling in Walnut Sector in Ukraine - Белей (Belei), Світлана Іванівна; Lutsiak, Vitalii; Hutsol, Taras; Kovalenko, Nataliia; Kwaśniewski, Dariusz; Kowalczyk, Zbigniew; Marusei, Tatiana (My University, 2021)
The main goal of this study was to provide a critical analysis of the oil and fat sub-complex for deep walnut processing, to determine and compare the profitability of enterprises’ activities under different business models for implementation in the agro-food value chain. The latter was considered as an important factor for the development of the domestic market of walnuts and export opportunities. Business modeling of the enterprise activity in the oil and fat sub-complex for deep walnut processing was carried out. The stages of production and marketing activities of the enterprise from the garden planting or the purchase of the processed raw materials to the sale of the processed raw materials and products obtained from walnut processing depending on the chosen business model were considered. A comparative analysis of profitability of the enterprise activity and absolute values of income and profitability indicators under various business models of the enterprise activity were shown. The most cost-effective business-model entailed the combination of walnut production and its processing, which will provide profitability of up to 4640.32% in the 20th year of the project implementation. The results of the given study are intended for the agricultural enterprises of central region of Ukraine.
Keywords: business model; profitability; walnut production; walnut processing; comparative analysis